Dietary intake of athletes seeking nutrition advice at a major international competition - Burkhart, S. J.; Pelly, F. E. (Nutrients, 2016)
International travel and short-term residence overseas is now a common feature of an elite athlete`s competition schedule, however, food choice away from home may be challenging and potentially impact on performance. Guidelines for dietary intake specific to competition exist for athletes, however, there is little evidence available to ascertain if athletes meet these recommendations during competition periods, particularly when food is provided in-house. During the Delhi 2010 Commonwealth Games, dietitians based in the dining hall recorded 24 h dietary recalls with all athletes who visited the nutrition kiosk. Analysis of dietary intake was conducted with FoodWorks (Xyris Pty Ltd., Brisbane, Australia). Overall, athletes reported consuming a median total daily energy intake of 8674 kJ (range 2384-18,009 kJ), with carbohydrate within the range of 1.0-9.0 g per kg of bodyweight (g/kg) (median = 3.8) and contributing to 50% total energy (TE) (range 14%-79%). Protein and fat intake ranged from 0.3-4.0 g/kg (median = 1.7) to 10-138 g (median = 67 g), and contributed to 21% TE (range 8%-48%) and 24% TE (range 8%-44%), respectively. Athletes reported consuming between 4 and 29 different food items (median = 15) in the previous 24 h period, with predominately discretionary, grains/cereals, meats, poultry, fish, eggs, and meat alternative items. This suggests that dairy, fruit, and vegetable intake may be suboptimal and intake of the micronutrients iron, zinc, calcium, and vitamins A and C may be of concern for a number of athletes